THE CENSORIAL MARK IN ANCIENT ROMAN MARITAL MATTERS - Tarwacka, Anna (Zeszyty Prawnicze, 2019)
This article is on the administration of the censor’s mark on Roman citizens who contracted inappropriate marriages in republican Rome. An examination of the source texts has led me to conclude that marriages contracted by members of the nobility with freedwomen or women with a bad reputation were considered unacceptable and were liable to a censor’s mark. That is why authors writing on Augustus’ reform of the marriage laws say that the Emperor permitted all the citizens except senators to marry a freedwoman.